Perceptions of the psychological experiences surrounding female genital mutilation/cutting (FGM/C) among the Izzi in Southeast Nigeria. (February 2020) - Omigbodun, Olayinka; Bella-Awusah, Tolulope; Groleau, Danielle; Abdulmalik, Jibril; Emma-Echiegu, Nkechi; Adedokun, Babatunde; Omigbodun, Akinyinka
Evidence about psychological experiences surrounding female genital mutilation/cutting (FGM/C) remains weak and inconclusive. This article is the first of a series that deploys qualitative methods to ascertain the psychological experiences associated with FGM/C through the lifecycle of women. Using the free listing method, 103 girls and women, aged 12 to 68 years from rural and urban Izzi communities in Southeastern Nigeria, produced narratives to articulate their perceptions of FGM/C. Sixty-one of them had undergone FGM/C while 42 had not. Data was analysed using thematic analysis and the emerging themes were related to experiences and disabilities in the psychological, physical, and social health domains. While physical experiences were mostly negative, psychological experiences emerged as both positive and negative. Positive experiences such as happiness, hopefulness, and improved self-esteem were commonly described in response to a rise in social status following FGM/C and relief from the stigma of not having undergone FGM/C. Less commonly reported were negative psychological experiences, e.g., shame when not cut, anxiety in anticipation of the procedure, and regret, sadness, and anger when complications arose from FGM/C. Some participants listed disruption of daily activities, chronic pain, and sleep and sexual difficulties occurring in the aftermath of FGM/C. Most participants did not list FGM/C as having a significant effect on their daily living activities. In light of the association of FGM/C with both positive and negative psychological experiences in the Izzi community, more in-depth study is required to enable policy makers and those campaigning for its complete eradication to rethink strategies and improve interventions.